PERAN KELEMBAGAAN LOKAL DALAM PENGELOLAAN SUMBERDAYA LAUT SEBAGAI UPAYA PENINGKATAN PEREKONOMIAN MASYARAKAT PESISIR (Studi Kasus di Kawasan Taman Nasional Wakatobi (TNW)) - Yusriadin; Tjandra Buana; Mardin; Muhammad Aldin (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2024)
The rise of threats or intersections from marine resource utilization activities that are not environmentally friendly and do not pay attention to the sustainability and sustainability of marine resources results in less economic stability of coastal communities. Therefore, it is necessary to manage and supervise the utilization of potential marine resources so as to ensure the sustainability of marine resources, improve and encourage economic strengthening of coastal communities, especially fishermen. The purpose of this study is to examine the role of local institutions in marine resources management as an effort to improve the economy of coastal communities in the Wakatobi National Park area. The informants used in this study were fishermen, members or heads of fishermen groups, members or heads of customary groups, members or heads of non-governmental organizations. The types of data used include primary data and secondary data. Data collection techniques use interviews, observations, Focus Group Discussion (FGD) and literature studies. The data analysis used in this paper is qualitative descriptive analysis. The results showed that the role of local institutions in marine resources management as an effort to improve the economy of coastal communities in the Wakatobi National Park area, namely: 1) socializing the use of environmentally friendly traditional fishing gear so as to maintain minimum size and fishing season, fish populations remain sustainable, maintain fish production in the long term; 2) apply marine management and protection methods based on local wisdom (Sasi Method); 3) Advancing conservation partnership programs as an effort to encourage community welfare and conservation area sustainability; 4) encourage the involvement of fishing groups in the processing and processing of catches such as fish drying, preservation or seafood processing; 5) Support local economic empowerment, create local jobs and help coastal communities overcome poverty through cooperation with financial institutions and training institutions in coastal economic enterprises; 6) supervise and regulate the sustainable use of marine resources based on indigenous peoples as an effort to maintain the carrying capacity of the environment, livelihoods or the main economic resources of coastal communities; and 7) help promote sustainable coastal and marine tourism.